High Entropy Cantor Alloys (HEAs) modification induced by tungsten alligation, heat treatment and deep cold plastic deformation (Fracture and Structural Integrity, 2022)
High Entropy Alloys (HEAs) is a unique class of materials that combine particular properties in a large-scale of temperatures, able to guarantee new unexplored materials and alloys with several potentially engineering applications (i.e. space and aerospace industries). As promising structural materials, HEAs consist of five or more principal elements. As a consequence of the monophasic microstructure which usually characterizes HEAs, these alloys offer an excellent combination of strength, strain hardening ability, good plasticity, ductility and fracture toughness especially at cryogenic temperatures better than the existing conventional metals and alloys. For the above reasons, the present work deals with Classic Cantor alloy, a well-known CoCrFeMnNi HEA, where mechanical properties were improved using low cost casting techniques and a combination of different metallurgical methodologies (heat treatment, cold working and adding alloying elements). A promising alloy element, tungsten, was used in the experimentation where mechanical and microstructural characterization were performed using different techniques
Keywords: High Entropy Alloy; Cantor; W alligation; heat treatment; cold working